Clinical awareness of therapeutic drug monitoring among medical students—A descriptive cross-sectional study - Amberkar Mohanbabu Vittalrao, Aditya Kumar Adhikarla, Sadhana N. Holla, Meena Kumari Kamalkishore, Seema Kumari Kamal Kishore (Journal of Applied Pharmaceutical Science, 2021)
“A doctor without effective clinical skills is a dodo knowledge.” Today’s budding medical student is tomorrow’s prolific doctor and the pillar of the health care system. The objective was to determine the level of medical students’ knowledge on therapeutic drug monitoring (TDM) and create awareness. This study was an institutional-based, descriptive cross-sectional study among the medical students and interns using self-designed, experts validated TDM questionnaire. The questionnaire was divided into Section A—Importance of TDM, Section B—Questions on the core concept, and Section C—On analysis, interpretation, measuring, monitoring, and limitations of TDM. We scored the outcomes for the framed positive and negative questions. On analyzing the grading of scores of students and interns, 11.3% (44/390) scored excellently, 59.5% (232/390) showed a good response, and 29.2% (114/390) reciprocated with a poor grade. We performed an analysis of responses of all three categories related to “most impactful and significant clinical concepts of TDM” requiring in-depth knowledge. The knowledge in medical students, including interns' stands average. The only way to improve this knowledge deficit by conducting well-designed training programs, implementing the concept of TDM so the students are made aware at the undergraduate level and become productive clinically.
Keywords: Awareness, curriculum, drug monitoring, pharmacokinetics, regimen.